A Comparative Legal Studies of Abortion Policies in Indonesia, Malaysia and England - Firzaa, Nur Ras (Universitas Muhammadiyah Yogyakarta, 2019)
This paper aims to address the issue of abortion from the perspective of Malaysian law, Indonesian law, English law and Islamic Jurisprudence. It will look into the three national laws to extricate ruling in regards to abortion and simultaneously making an effort to have knowledge on the ruling of abortion taking into consideration of Islamic Jurisprudence. This paper also critically discussed the law cases that had been decided by courts in each jurisdiction and made comparison to identify both the similarities and dissimilarities. The paper had reached some fundamental outcome which are: Malaysian law and Indonesian law impede abortion except in case of necessity and when there are reasonable justifications, however, English law provides that abortion can be done if the fetus is less than 24 weeks of pregnancy. In addition, the scholars are in consensus that abortion is prohibit when the fetus starts to breath.